Flame retardant properties and mechanism of PLA/P-PPD -Ph /ECE conjugated flame retardant composites - Tan, Yanyan; Zhang, Daohai; Xue, Yu; Zhan, Xiao; Tan, Fang; Qin, Shuhao (Frontiers in Chemistry, 2023)
A two-step synthesis of 4, 4'-{1'',4''-phenylene-bis[amido-(10'' ''-oxo-10'''-hydro-9'''-oxa-10'''λ5-phosphafi-10'''-yl)-methyl]}-diphenol (P-PPD-Ph), and the chemical structure of the prepared P-PPD-Ph was characterized by FTIR, 1 H NMR, 31 P NMR. The structures of the prepared P-PPD-Ph were characterized by FTIR, 1 H NMR and 31 P NMR, demonstrating the successful synthesis of the phosphoramidite flame retardant P-PPD-Ph. The PLA/P-PPD-Ph/ECE conjugated flame retardant composites were produced by co-extrusion of different levels of epoxy chain extender (ECE) with 5 wt% P-PPD-Ph added to poly(lactic acid) (PLA). PLA/P-PPD-Ph/ECE conjugated flame retardant composites were produced by blending and extruding different levels of epoxy chain extender (ECE) with 5 wt% of the phosphorus heterophilic flame retardant P-PPD-Ph into poly(lactic acid) (PLA). Fourier transform infrared spectroscopy (FTIR), thermogravimetry (TG), vertical combustion test (UL-94), limiting oxygen index (LOI), cone calorimetry, scanning electron microscopy (SEM) EDS and mechanical property tests were used to characterize the structure, thermal properties, flame retardancy and mechanical properties of PLA/P-PPD-Ph/ECE conjugated flame retardant composites. The results showed that as the ECE content increased, the carbon residue rate of the composite increased from 1.6% to 3.3% and the LOI value increased from 29.8% to 32.6%. The cross-linking reaction occurred between P-PPD-Ph and PLA and the reaction sites increased, resulting in more phosphorus-containing materials. P-PPD-Ph and PLA underwent a cross-linking reaction and as the reaction sites multiplied, more phosphorus-containing free radicals were produced on the PLA molecular chain, which strengthened the condensed phase flame retardant effect of PLA flame retardant composites and increased their bending strength, tensile strength and impact strength.